Legal means of initiating constitutional proceedings before the Constitutional Court: An analytical and comparative study - عمر, شۆڕش حسن; أحمد, ڕووبار مجيد (Sulaimani Journal for Humanities, 2019)
That the subject of legal means to move the constitutional case before the Constitutional Court is of great importance, because through it enter the theoretical texts in the field of practical and dynamic application, and these methods differ from one state to another according to the constitutional system or style that is consistent with the constitutional judiciary, For this purpose, we have made a comparison between the constitutional judiciary in Egypt, Kuwait and Iraq, and we found that in Egypt the constitutional action is moved according to three methods, including automatic referral by the court of the subject and referral based on payment from one of the litigants in the substantive case before the court of the subject But ESP The constitutional order in Egypt is the means of direct constitutional action before the Supreme Constitutional Court. In Kuwait, the Constitutional Court is contacted by way of automatic referral from the Court of Appeal and the assignment on the basis of a payment made by one of the litigants in the substantive and direct constitutional proceedings before the Constitutional Court And in Iraq, the constitutional action is moved by means of automatic referral by the Court of Appeal and payment associated with referral to the Federal Supreme Court and the original or direct constitutional action by the official authorities and persons.